Vpliv epidemije na socialne razmere prebolelih po COVID-19 - Ronchi, Katja (Rehabilitacija (Ljubljana), 2021)
Background: The declaration of the SARS-CoV-2 virus epidemic in Slovenia had a significant impact on the social context of individuals. In this paper, we assess the consequences of the disease and the measures taken to contain the epidemic in Slovenia on the social conditions of those COVID-19 survivors who were admitted to rehabilitation at the University Rehabilitation Institute in Ljubljana. Methods: The study included individuals who were admitted to our Institute after a severe course of COVID-19 in the period from November 2020 to the beginning of April 2021. Descriptive statistics were calculated and graphical presentations were made for the variables considered. Results: The study included 43 individuals, 12 women and 31 men, with a mean age of 61 years (range 37-81 years). Among them, 22 were retired and the remaining 21 were employed. Among the 21 employed, there were 18 for whom return to work was difficult. Six were unemployed, one of them due to the impact of the epidemic. Of the 14 permanent employees, one person was on hold due to the impact of the epidemic. One person, who was otherwise employed on a temporary basis, was on hold for other reasons. The impact of the epidemic on household income was felt by 20 people, including two people severely and one person slightly. For nine individuals, the informal social network decreased due to the infection. After discharge, in all cases but one, an informal social network for support and assistance in the home environment became involved. For five individuals, a formal support and assistance network had to be activated. Conclusion: The consequences of the disease and the measures taken to contain the epidemic in Slovenia affected the social situation of the COVID-19 survivors admitted to rehabilitation at our Institute. Identification of strengths and sources of help in an individual's life, early involvement of an informal social network in the rehabilitation process, activation of social resources from the environment and setting specific goals for the working population proved to be key elements in preventing deterioration of social and economic conditions of COVID-19 survivors.
Keywords: COVID-19; hujši potek COVID-19; informal social network; neformalna socialna mreža; rehabilitacija; Rehabilitation; return to work; severe course of COVID-19; social resources; socialni viri; socialno-ekonomski status; socioeconomic status; vračanje na delo